Bisacodyl in Stimulant Laxatives Can Induce Estrogen Agonist/Antagonist Activity in Breast Cancer Cells in Culture - Ngo, Lynda (J Endocr Soc, 2021)
Exposure to xenobiotic estrogens has the potential to induce estrogen activity that may contribute to a range of undesired physiological effects including the stimulation of estrogen responsive tumors. We have previously determined that extracts of OTC medications containing the stimulant laxative bisacodyl induce estrogenic activity in tissue culture bioassays. In this study, we tested the hypothesis that bisacodyl is responsible for the estrogen activity of these extracts and then characterized these effects. Ethanol extracts and dilutions were prepared from OTC medications containing Bisacodyl (1 gm:1 ml). The estrogen agonist and antagonist activity of each extract, as well as bisacodyl and then metabolite DA-bisacodyl was determined using the T47dkbluc estrogen reporter gene and the MCF-7 E3 estrogen responsive proliferation assays. LC-MS analysis was used to determine bisacodyl and DA-bisacodyl concentration in extracts as well as to trace the metabolism of bisacodyl to DA-bisacodyl in the cell culture bioassays. Molecular modeling “docking” simulations of the interactions of bisacodyl and the metabolite DA-bisacodyl with the estrogen receptor (ER) ligand binding domain was performed using MOE from Chemical Computing Group. Bisacodyl and the metabolite DA-bisacodyl induced mixed agonist/antagonist activity in MCF-7 E3 estrogen responsive proliferation assay similar to 4OH-tamoxifen. At the same time, both compounds stimulated only minimal estrogen activity in the T47dkbluc estrogen reporter gene assay. LC-MS analysis determinations identified that almost all bisacodyl was converted to the dihydroxy metabolite DA-bisacodyl in cell culture bioassays. Molecular modeling “docking” simulations determined that while bisacodyl does not fit into the agonist (estradiol) or antagonist (4OH-tamoxifen) conformations of the estrogen receptor ligand binding site, the metabolite DA-bisacodyl may fit into the antagonist induced binding pocket of the ER in a reasonable way. This study characterizes the observed estrogen activity of extracts from OTC medications containing bisacodyl as resulting from the bisacodyl metabolite DA-bisacodyl interacting with the estrogen receptor. Thus, bisacodyl is an OTC medication active ingredient that has potential to induce side effects and or toxicity involving estrogen signalling. The capacity for medications containing bisacodyl or other estrogenic substances to induce estrogen activity in patients is unclear. At the same time, consumers and practitioners should be aware of the potential estrogen activity of bisacodyl containing products.